Opportunistic activation of TRP receptors by endogenous lipids: Exploiting lipidomics to understand TRP receptor cellular communication - Bradshaw, Heather B. (2012)
Transient receptor potential channels (TRPs) form a large family of ubiquitous non-selective cation channels that function as cellular sensors and in many cases regulate intracellular calcium. Identification of the endogenous ligands that activate these TRP receptors is still under intense investigation with the majority of these channels still remaining “orphans”. That these channels respond to a variety of external stimuli (e.g. plant-derived lipids, changes in temperature, and changes in pH) provides a framework for their abilities as cellular sensors, however, the mechanism of direct activation is still under much debate and research. In the cases where endogenous ligands (predominately lipids) have shown direct activation of a channel, multiple ligands have been shown to activate the same channel suggesting that these receptors are “promiscuous” in nature. Lipidomics of a growing class of endogenous lipids, N-acyl amides, the most famous of which is N-arachidonoyl ethanolamine (the endogenous cannabinoid, Anandamide) is providing a novel set of ligands that have been shown to activate some members of the TRP family and have the potential to deorphanize many more. Here it is argued that activation of TRPV receptors, a subset of the larger family of TRPs, by multiple endogenous lipids that are structurally analogous is a model system to drive our understanding that many TRP receptors are not promiscuous, but are more characteristically “opportunistic” in nature; exploiting the structural similarity and biosynthesis of a narrow range of analogous endogenous lipids. In addition, this manuscript will compare the activation properties of TRPC5 to the activity profile of an “orphan” lipid, N-palmitoyl glycine; further demonstrating that lipidomics aimed at expanding our knowledge of the family of N-acyl amides has the potential to provide novel avenues of research for TRP receptors.